2022
DOI: 10.3390/su14073916
|View full text |Cite
|
Sign up to set email alerts
|

The Public’s Understanding of Superfoods

Abstract: The term “superfood” is linked to food that is beneficial to health. However, there is no legal or clear scientific definition, and little is known about individual perceptions of this food group. Therefore, an online survey was conducted (n = 1006 respondents) to assess the public’s understanding of superfoods in Germany, including (a) the conceptual understanding of the term “superfood”, (b) corresponding consumption behavior, and (c) the risk–benefit appraisal. In total, 70% of respondents were aware of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
3
1
1
Order By: Relevance
“…Higher income is further assumed to correlate with a higher average age of avocado consumers. Although studies on superfoods have found that consumption and positive attitudes towards such products tend to be associated with a younger age ( 18 , 107 ), these samples were older overall, whereas respondents in the present study were relatively young. An interesting finding, however, is that a large proportion of avocado consumers are located in urban regions.…”
Section: Discussioncontrasting
confidence: 81%
“…Higher income is further assumed to correlate with a higher average age of avocado consumers. Although studies on superfoods have found that consumption and positive attitudes towards such products tend to be associated with a younger age ( 18 , 107 ), these samples were older overall, whereas respondents in the present study were relatively young. An interesting finding, however, is that a large proportion of avocado consumers are located in urban regions.…”
Section: Discussioncontrasting
confidence: 81%
“…The term is commonly used in informal communication, on social media and by popular influencers, which increases the popularity of a wide variety of foods [4]. Although the scientific literature endorses the health benefits of 'superfoods', other considerations must be contemplated, such as the factors that influence the chemical composition of foods and the potential health risks of consumption of some 'superfoods' [5].…”
Section: Introductionmentioning
confidence: 99%
“…The classification of foodstuffs in the category of 'superfoods' could affect the demand, the consumption and the attitudes of consumers towards them; many studies related to these effects can be found [2,3,5,9]. Moreover, a great attention has been paid in recent years to the new digital sources that people use for getting information about health, nutrition and food [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of many oxidative diseases, a lot of the so-called 'superfoods' have also been emerging [24]. Although there is no clear scientific basis, superfoods are foods that are considered superior owing to their bioactive properties [25]. One such superfood is barley.…”
Section: Introductionmentioning
confidence: 99%